The creativity of monuments: the case of bistable Belarusian identity - Beržiūnas, Valentinas (Creativity Studies, 2025)
During the last decades, Belarus has experienced a wave of monument construction, i.e., the monuments as creative practices through which certain historical, cultural and political meanings are constructed and articulated. The process confirms some scientists’ insights that the Belarusian identity is actively created today. However, the scientists who are interested in its construction on a practical level have not paid attention to the process of monument creation in Belarus as it also creates and articulates state identity. The analysis of the monument-making process has revealed that three identity narratives co-exist in Belarus: national-cultural and two political-historical ones, i.e., commonality with Russia and political independence from Russia. The potential contradiction of these political-historical narratives shows that the Belarusian identity is in a dichotomous and uncertain state. Although the spread of the political independence from Russia narrative allows us to talk about the existence of an independent national identity of Belarus (one of the most prominent manifestations was the mass protests in 2020, unpredicted by many scientists) in parallel with the existence of a strong historical-political narrative of commonality with Russia, the identity of Belarus remains in a bistable condition. For this reason, the further development of the Belarusian identity remains uncertain in the long-term perspective.